Methodological Analysis of Soil Respiration: An Approach to Interpretation - Montoya-Jasso, Víctor Manuel; Ordaz-Chaparro, Víctor Manuel; Benedicto-Valdés, Gerardo Sergio; Ruiz-Bello, Alejandrina; Arreola-Tostado, Jesús Manuel (REVISTA TERRA LATINOAMERICANA, 2024)
A methodology is proposed for the interpretation of gas emissions that come from the soil based on the integration of the primary actors in the production systems and members of the ecosystems. The methodology presents data in units that are easy to understand by people outside the study of gas emissions in different ecosystems and production systems, and optimizes the calculation of small and medium scale predictions through estimation with a high degree of ratio and mathematical adjustment. From the use of the ideal gas equation, it was possible to develop the methodology to obtain a conversion factor taking into account variables such as the pressure and temperature of the site where the gas quantification experiment is being carried out. With the aforementioned, it is easier to obtain the constant of the molar volume of the container used and data transformation to ensure compliance with basic statistical parameters such as normality, variance similar to zero, and confidence intervals with less deviation. The present methodological development represents a tool for the generation of data at the laboratory and plot level with mathematical support that facilitates the execution of mathematical models in comparison with other methodologies.